EKSPLORASI FAKTOR PENENTU TINGKAT AGRESIVITAS PAJAK DALAM PERSPEKTIF TEORI KEUANGAN - Samiati, Tita; Rahmawati, Teti; Nurhayati, Neni; Maryami, Mimi (Jurnal Riset Keuangan dan Akuntansi, 2024)
The purpose of this study is to analyze the factors affecting tax aggressiveness. The research method used is the descriptive verification method. The population in this study is manufacturing companies in various industrial sectors as many as 51 companies listed on the Indonesia Stock Exchange in 2016-2020. The sample used is the annual financial statements of companies in various industrial sectors as many as 34 companies using purposive sampling techniques. The analysis technique used in this study is panel data analysis technique. Profitability has a positive and significant effect on tax aggressiveness, liquidity has a positive and significant effect on tax aggressiveness, leverage has a negative and significant effect on tax aggressiveness Keywords: Tax Aggressiveness, Leverage Ratio, Liquidity Ratio, Profitability Ratio